2014
DOI: 10.1063/1.4871578
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous carbon doping of magnesium diboride by high-temperature, high-pressure synthesis

Abstract: We have used high-pressure, high-temperature synthesis at 1500–1700 °C and 10 MPa to create homogeneously C-substituted MgB2 from a B4C + Mg mixture. X-ray diffraction analysis showed large peak-shifts consistent with a decrease in the a lattice parameter for the B4C-derived MgB2 as compared to an undoped sample (0.033–0.037 Å, depending on the sample). Microstructural investigation showed a three-phase mixture in the B4C-derived ingots: MgB2−xCx (with 0.178 < x < 0.195), MgB2C2, and Mg. The carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…For the Dy 2 O 3 added sample HTP-DY, similar to Chen’s report 17 , the lattice parameters a and c did not change with Dy 2 O 3 addition. Similarly, for the MB 2 added samples, even though both lattice parameters a and c were slightly changed, these changes were very small and none of the doped samples obeyed Vegard’s law, unlike C-doped MgB 2 HTP bulks 6 . Therefore it seems that even under HTP processing the metal borides (ZrB 2 , TiB 2 and NbB 2 ) mainly acted as impurity phases and did not form homogeneous solid solutions with MgB 2 , at least not to an extent detectable by XRD.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…For the Dy 2 O 3 added sample HTP-DY, similar to Chen’s report 17 , the lattice parameters a and c did not change with Dy 2 O 3 addition. Similarly, for the MB 2 added samples, even though both lattice parameters a and c were slightly changed, these changes were very small and none of the doped samples obeyed Vegard’s law, unlike C-doped MgB 2 HTP bulks 6 . Therefore it seems that even under HTP processing the metal borides (ZrB 2 , TiB 2 and NbB 2 ) mainly acted as impurity phases and did not form homogeneous solid solutions with MgB 2 , at least not to an extent detectable by XRD.…”
Section: Resultsmentioning
confidence: 92%
“…Extensive efforts have been expended in doping MgB 2 to enhance its superconductive properties, particularly its upper critical field, B c2 . The substitution of C for B has been shown to significantly increase MgB 2 ’s B c2 beyond that of the unalloyed sample 1 2 3 4 5 6 . Unfortunately, C doping is successful only at low temperatures (<20 K) since it reduces T c and increases electron impurity scattering only in the σ band, leaving the high temperature (>20 K) B c2 unchanged or even reduced.…”
mentioning
confidence: 99%
“…A detailed report on X‐ray tomography on malic acid doping on MgB 2 tapes confirmed that the carbon from the malic acid uniformly encapsulates boron, preventing boron agglomeration which lead to the void density being decreased from 50 to 40%, which is very important for the production of bulk MgB 2 material for superconducting super‐magnet applications . In addition, recent work on TEM observations of the MgB 2 material proved that samples sintered at low temperatures exhibited improved critical current density . The nanosized MgB 2 grains are quite important for further improvement of the flux pinning of the sintered material which is governed by the sintering time and the sintering temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The main reason is the limitation (<1 at.% carbon) of the EELS resolution. A recent work on the STEM observation of a MgB 2 specimen sintered at a low temperature (650°C) and short sintering time (<1 h) still remains unclear because the majority of carbon was found to be mainly located at the grain boundaries (Susner et al 2014). In this work, as an extension of our previous work, detailed structural analysis and microstructure observations have been further carried out with an electrical current carrying property of a MgB 2 superconductor.…”
mentioning
confidence: 79%